Case Report: De novo multiple intracranial aneurysms following extracranial–intracranial bypass and proximal occlusion for a giant serpentine aneurysm - Xu, Hui; Latour, Kristy; Xu, Bin; Fontanella, Marco Maria; Xu, Feng (Frontiers in Surgery, 2025)
BackgroundCarotid artery occlusion, whether therapeutic, iatrogenic, atherosclerotic, or congenital, induces profound hemodynamic changes in the cerebral circulation. Collateral channels within the circle of Willis compensate to maintain cerebral perfusion; however, the resulting increases in flow velocity, wall shear stress, and pressure gradients are believed to ultimately contribute to aneurysm formation. While de novo aneurysms after hunterian ligation have been described, they typically occur years after treatment. The early occurrence of multiple aneurysms following parent artery occlusion combined with extracranial-intracranial (EC-IC) bypass has seldom been reported. Here, we report a unique case of multiple, non-anastomotic MCA aneurysms developing early after double-barrel bypass and proximal clipping.Case descriptionA 27-year-old male with severe headache was found to have a partially thrombosed giant serpentine aneurysm (GSA) of the left M2 inferior trunk. The patient underwent double-barrel superficial temporal artery–middle cerebral artery (STA–MCA) bypass followed by proximal clipping. Postoperative imaging confirmed complete exclusion of the aneurysm and excellent bypass patency. Three months later, acute aphasia and right hemiparesis developed. Angiography revealed two newly formed aneurysms along the left MCA bifurcation point and the M2 superior trunk, which were successfully treated with endovascular coil embolization and parent artery occlusion. At nine-month follow-up, the patient remained neurologically intact with patent bypass grafts and no aneurysm recurrence.ConclusionsThis case illustrates an unusual pattern of early, multiple, non-anastomotic de novo MCA aneurysms developing after double-barrel STA–MCA bypass and proximal clipping. The findings highlight how revascularization can alter local pressure gradients and redistribute flow in ways that relieve hemodynamic stress on classic collateral pathways yet create new regions of focal wall shear stress along the ipsilateral MCA.